2009
DOI: 10.1172/jci39387
|View full text |Cite
|
Sign up to set email alerts
|

Tregs control the development of symptomatic West Nile virus infection in humans and mice

Abstract: West Nile virus (WNV) causes asymptomatic infection in most humans, but for undefined reasons, approximately 20% of immunocompetent individuals develop West Nile fever, a potentially debilitating febrile illness, and approximately 1% develop neuroinvasive disease syndromes. Notably, since its emergence in 1999, WNV has become the leading cause of epidemic viral encephalitis in North America. We hypothesized that CD4 + Tregs might be differentially regulated in subjects with symptomatic compared with those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
216
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(233 citation statements)
references
References 59 publications
13
216
0
4
Order By: Relevance
“…In another form of viral hemorrhagic fever, that caused by acute dengue virus infection, patients exhibited increased numbers of regulatory CD4 T cells in peripheral blood within 1 to 10 days of the first symptoms compared to the numbers seen at later phases of the disease (20). Furthermore, in acute infection of humans by West Nile virus, a virus with the capacity to infect endothelial cells (40), numbers of regulatory CD4 T cells in peripheral blood were unchanged early after symptom development (assessed, on average, at day 15 after symptom debut) but increased 2-fold during the next 3 months (18). Since FoxP3 can be transiently expressed in nonregulatory activated CD4 T cells (41), in the current study, we used multiple phenotypic markers (FoxP3, CD25, and CD127) to ensure that we were studying T cells of a regulatory phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another form of viral hemorrhagic fever, that caused by acute dengue virus infection, patients exhibited increased numbers of regulatory CD4 T cells in peripheral blood within 1 to 10 days of the first symptoms compared to the numbers seen at later phases of the disease (20). Furthermore, in acute infection of humans by West Nile virus, a virus with the capacity to infect endothelial cells (40), numbers of regulatory CD4 T cells in peripheral blood were unchanged early after symptom development (assessed, on average, at day 15 after symptom debut) but increased 2-fold during the next 3 months (18). Since FoxP3 can be transiently expressed in nonregulatory activated CD4 T cells (41), in the current study, we used multiple phenotypic markers (FoxP3, CD25, and CD127) to ensure that we were studying T cells of a regulatory phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Although the absolute numbers of CD4 T cells with a regulatory phenotype increased slightly over time, we could not detect a specific increase of these cells occurring within the first 2 months after symptom debut in the hantavirus-infected patients. Therefore, whereas regulatory CD4 T cell numbers increased during the acute and follow-up phases of West Nile and dengue virus infections (18,20)…”
Section: Discussionmentioning
confidence: 99%
“…For instance, intracranial, but not peripheral transfer, of anti-JEV effector cells protected mice from lethal intracranial challenge with JEV [237,238]. Nonetheless, CD8 T cells contribute to both recovery and immunopathology of WNV infection [239], and the presence of regulatory T cells in the CNS of mice infected with WNV is associated with reduced immunopathology both in humans and mice [240]. In addition, the CD8 T-cell response was not required for clearance of RVFV from the CNS [229], or for protection against lethal VEEV encephalitis [231].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%
“…Depending on the situation, the presence of Tregs can be either beneficial or detrimental for the host. Tregs can prevent collateral tissue damage (11,12) and autoimmunity (13) during viral infections, but it has also been shown that Tregs can suppress antiviral immune responses, thus facilitating chronic viral diseases (14,15). Corresponding studies with animal infection models showed that anti-CD25 Ab-mediated depletion of Tregs supported systemic antiviral CD8 + T cell responses and subsequent clearance of the pathogen (16).…”
Section: Introductionmentioning
confidence: 99%